Financial inclusion, regulation, and education in Sri Lanka - Saman Kelegama; Ganga Tilakaratna (Asian Development Bank Institute (ADBI), 2014)
Sri Lanka has achieved a high level of financial inclusion compared to other South Asian countries. Its financial sector comprises a wide range of financial institutions providing financial services such as loans, savings, pawning, leasing and finance, and remittance and money transfer facilities. There is also evidence that a larger share of households in Sri Lanka accesses multiple financial institutions for their credit and savings needs. However, the use of insurance services, ATM facilities, e-payments, and mobile banking, is relatively low. Financial education is ad hoc and lags behind financial innovation and new products. The information technology (IT) literacy rate is only 35% in Sri Lanka, and with the growing IT-finance nexus, financial awareness and education have become all the more important. Strengthening the regulatory framework governing the microfinance sector and client protection is also crucial for improving financial inclusion in Sri Lanka. Much scope remains to improve financial inclusion, particularly related to cost and quality of financial services provided, and the sustainability of financial institutions.
Keywords: G20; G21; G28; 330; financial services; financial inclusion; financial education; financial regulation; microfinance